Evaluation of the activity of bispirazoles against recombinant Trypanosoma cruzi strains expressing ß-galactosidase - Galarza Jarrín, Ambar Nicol (2023)
Background: Nifurtimox and benznidazole are the only drugs currently approved to treat Chagas disease, caused Trypanosoma cruzi. However, they display unsatisfactory efficacy and induce undesirable side effects. Therefore, identifying new compounds with specific activity against T. cruzi is of great interest.Methods. The in vitro activity of twenty-five bispirazoles was evaluated against intracellular amastigotes of the recombinant Tulahuen ß-gal strain of T. cruzi. Their cytotocicity against mammalian cells was evaluated via resazurin reduction assays. BNZ was used as a reference drug.Results: In the initial two repetitions of the screen, one bispirazole (2X) presented specific in vitro activity against T. cruzi, with an IC50 value of 3,416 µM and no measurable cytotoxicity at concentrations up 100 µM. BNZ, employed as reference drug, displayed a IC50 of 4,23 µM and a CC50 up to 100 µM. Compound 2X´s activity was not reproducible in subsequent replicates.Conclusions: One evaluated compound was selectively toxic against intracellular T. cruzi amastigotes in vitro and did not show cytotoxic activity against mammalian cells. Its IC50 value is comparable to those obtained for BNZ, the reference drug. Further studies are warranted to confirm the anti-T. cruzi activity of compound 2X.